Pengaruh Diversifikasi Pendapatan, Firm Specific, dan Makroekonomi terhadap Kinerja Perbankan di BEI - Maharestu, Aruna Ardya; Jannatul Mawah, Nana; Nurhaliza, Riqqah; Lestari, Henny Setyo (Economic Reviews Journal, 2025)
This study aims to analyze the impact of income diversification, firm-specific factors, and macroeconomic factors on the performance of banks listed on the Indonesia Stock Exchange. The firm-specific factors examined include bank size, capital structure, asset growth rate, loan loss provisions, and management efficiency, while the macroeconomic factors include economic growth rate and inflation. The increasingly competitive banking industry encourages banks to shift their orientation from labor-based business to knowledge-based business, necessitating a comprehensive performance evaluation. Return on Assets (ROA) is used as an indicator to measure bank performance. This study uses a quantitative approach with data from banks listed on the Indonesia Stock Exchange. The results of the study indicate that income diversification, bank size, capital structure, asset growth rate, loan loss provisions, management efficiency, economic growth rate, and inflation rate do affect company performance, and capital structure have an effect on company performance.